2020
DOI: 10.1523/jneurosci.1046-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Sickness Disrupts the Sleep-Regulating Adenosine System

Abstract: Patients with sleeping sickness, caused by the parasite Trypanosoma brucei, have disruptions in both sleep timing and sleep architecture. However, the underlying cause of these sleep disturbances is not well understood. Here, we assessed the sleep architecture of male mice infected with T. brucei and found that infected mice had drastically altered sleep patterns. Interestingly, T. brucei-infected mice also had a reduced homeostatic sleep response to sleep deprivation, a response modulated by the adenosine sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…Circadian rhythms can be modulated by temperature, nutrition, immune challenges, social interactions, and mechanosensory stimulation, among other factors [22][23][24][25][26]. Similarly, the sleep homeostat and its response to sleep deprivation can be affected by stress, social cues, and infections [27][28][29]. Process C and Process S are separable, but there is evidence of interaction between them [6].…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythms can be modulated by temperature, nutrition, immune challenges, social interactions, and mechanosensory stimulation, among other factors [22][23][24][25][26]. Similarly, the sleep homeostat and its response to sleep deprivation can be affected by stress, social cues, and infections [27][28][29]. Process C and Process S are separable, but there is evidence of interaction between them [6].…”
Section: Introductionmentioning
confidence: 99%
“…T . b. rhodesiense infections are known to disrupt the circadian rhythm which results in sleep disturbance in infected individuals (4, 22-24). For this, we observed that circadian rhythm CIPC ( clock interacting pacemaker ) was differentially expressed (padj<1.59E-6) and down regulated (log2FC -1.9) suggesting a disruption of circadian rhythm in patients with stage 1 disease compared to healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Another target gene that we identified in the present study was ADORA1 , which regulates various biological functions, including the mechanisms underlying sleep [ 101 , 102 ], and psychiatric disorders including depression [ 103 , 104 , 105 ]. ADORA1 activation has been found to induce antidepressant-like effects [ 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%